Process of programming studying process in the context of limited attention field - Holovin, Mykola B.; Golovina, Nelia M. (Луцький національний технічний університет, 2015)
The processes of programming studying in the context of peculiarities of thinking were researched. These peculiarities are conditioned by the limitation of the attention field, and structure of studying material. Attention field and consciousness are connected by the short - term memory. Three component memory model and conception about evaluation of memory field size, through the magic number of Miller were used for explanation of studying processes. The explanation of three component memory model through peculiarities of brain structure is presented. In particular cyclical stimulation of limbic system was regarded as an embodiment of short - term memory. The localization of long-term memory traces and their hierarchical organization are also researched. This approach gave the possibility to connect in one model peculiarities of brain functioning, consciousness phenomenon, conceptions of education and emotional sphere of student. Original part of the research is related to graphical formalization of cognitive hierarchical scheme of long - term memory. Evolution of formation of this scheme is regarded in the article through the prism of educational strategies from general to concrete and from concrete to general.

Досліджувалися процеси навчання програмування в контексті особливостей мислення людини. Ці особливості обумовлені обмеженістю її поля уваги, а також структурою її знань. Поле уваги і свідомість пов'язані з короткочасною пам'яттю. Для пояснення процесів навчання в роботі використовуються трьохкомпонентна модель пам'яті і концепція оцінки розміру короткочасної пам'яті, через магічне число Міллера. Представлено пояснення механізму трикомпонентної моделі пам'яті через особливості будови мозку. Зокрема, циклічне збудження в лімбічної системи мозку розглядалося, як втілення короткочасної пам'яті. Розглядалась також ієрархічна специфіка організації довготривалої декларативної пам'яті. Цей підхід дав можливість зв'язати в одній моделі особливості функціонування мозку, феномен свідомості і поля уваги, концепції навчання, структуру знань, емоційну сферу учня. Оригінальна частина роботи стосується графічної формалізації когнітивної ієрархічної схеми в довгостроковій пам'яті. Еволюція формування цієї схеми розглядається в роботі через призму стратегій навчання від загального до конкретного і від конкретного до загального.
Keywords: 013.77:004.42; 37.013.03:004. 588(073)